2018
DOI: 10.1038/s41375-018-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

Drugging the lncRNA MALAT1 via LNA gapmeR ASO inhibits gene expression of proteasome subunits and triggers anti-multiple myeloma activity

Abstract: The biological role and therapeutic potential of long non-coding RNAs (lncRNAs) in multiple myeloma (MM) are still to be investigated. Here, we studied the functional significance and the druggability of the oncogenic lncRNA MALAT1 in MM. Targeting MALAT1 by novel LNA-gapmeR antisense oligonucleotide antagonized MM cell proliferation and triggered apoptosis both in vitro and in vivo in a murine xenograft model of human MM. Of note, antagonism of MALAT1 downmodulated the two major transcriptional activators of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
150
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 204 publications
(157 citation statements)
references
References 38 publications
1
150
0
Order By: Relevance
“…We found that some of the few genes deregulated in the FAM46C KO clones, such as MAGED1, RHOBTB1 and MALAT1 , had previously been associated with cell migration MALAT1 was found to be up‐regulated by FAM46C inactivation in the three HMCLs used in this study. This lncRNA was overexpressed in a wide variety of solid tumours and also in haematological malignancies, including MM . Moreover, high levels of expression of MALAT1 in MM have been associated with the onset of the disease, progression from normal PCs to MM and extramedullary dissemination .…”
Section: Discussionmentioning
confidence: 99%
“…We found that some of the few genes deregulated in the FAM46C KO clones, such as MAGED1, RHOBTB1 and MALAT1 , had previously been associated with cell migration MALAT1 was found to be up‐regulated by FAM46C inactivation in the three HMCLs used in this study. This lncRNA was overexpressed in a wide variety of solid tumours and also in haematological malignancies, including MM . Moreover, high levels of expression of MALAT1 in MM have been associated with the onset of the disease, progression from normal PCs to MM and extramedullary dissemination .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, we established that MALAT1 interacts with EZH2 to regulate KEAP1 expression, triggering a KEAP1-dependent induction of NRF1/2, two relevant transcriptional activators of proteasome subunit genes [152]. As a corollary of our work, we provided evidence of MALAT1 druggability using LNA gapmeRs in vitro and in vivo in NOD-SCID mice bearing MM xenografts [152]. Hu et al reported that MALAT1 acts as a scaffold in the formation of PARP1/LIG3 complexes that recognize DSBs on DNA and activate the alternative non-homologous end joining (A-NHEJ) DNA repair in MM cells [151].…”
Section: Lncrnasmentioning
confidence: 99%
“…To date, only a few lncRNAs have been functionally investigated in MM-including MALAT1 [151][152][153], NEAT1 [154,155], CCAT1 [156] and H19 [157,158]. Importantly, different reports converge in defining the oncogenic role of MALAT1 in MM, which was found upregulated during the progression from intra-medullary to extra-medullary disease, with the higher levels associated with shorter OS and PFS [153].…”
Section: Lncrnasmentioning
confidence: 99%
See 2 more Smart Citations